STRATEGY FOR STRENGTHENING CHARACTER EDUCATION IN FORMING AN ATTITUDE OF RELIGIOUS MODERATION KILAT PASRAMAN STUDENTS BANUROJA VILLAGE-GORONTALO: Strengthening Strategy, Character Education, Religious Moderation - Sulastra, I Made Sulastra; Yasa, I Made Wiguna; Putra, I Gede Garbha (UHN IGB Sugriwa Denpasar, 2024)
Religious moderation character education must start early, especially in heterogeneous areas or communities such as in Gorontalo Province. Religious moderation character education is carried out through three domains, namely education in the family, education in schools, and education in the community. Community support in Hindu religious education is through the provision of non-formal education in the form of pasraman. The purpose of this research is to find out the form of strategies to strengthen character education in forming an attitude of religious moderation, knowing the constraints and efforts and understanding the implications. This research method uses a type of qualitative research. This research was conducted at the Kilat Pasraman, Banuroja Village. Data collection techniques were obtained from observation, interviews, literature studies and document studies. Based on the results of this study, a strategy for strengthening character education in forming an attitude of religious moderation at the Kilat Village Islamic Boarding School in Banuroja Village is carried out by means of lesson planning, learning materials and learning implementation. Constraints include management of time allocation, distance to be covered and also learning facilities. Efforts made to overcome these obstacles apply a personal approach to optimize learning time, provide time flexibility for students, make use of the facilities and infrastructure they have. Implementation of the character of religious moderation through respect and appreciation, acceptance of differences and tolerance, helping, willing to share, polite, and humble. Implementation in learning is done with the lecture method, question and answer and practice is done with skills training.